Una comparación de la separabilidad de la cláusula arbitral del contrato LIca y de la ley modelo CNUDMI - Atefeh Darami Zadeh; Shapur Farhangpur (Universidad Hemisferios, 2018)
The aim of the paper was to investigate the independence of the arbitration clause from the main contract in the International Commercial Arbitration Law of Iran with a comparative study in the UNCITRAL model law. The effectiveness of this type of procedure, its coordination with the specific objectives and the special status of international traders has led to their increasing willingness to use this legal solution. We use a comparative method, quasi-experimental, to describe similarities and differences in variables in two or more existing groups in a natural setting; it resembles an experiment as it uses manipulation but lacks random assignment of individual subjects. This study begins analyzing international arbitration and the UNCITRAL model rules (Chapters I to VI), then reviewing the national arbitration (Chapter V); thus, the effects of the principle of independence of the arbitration clause can be seen (Chapter VII) and, later, the problems that arise (Chapters VIII to X). Even so, the main conclusion is that the parties usually agree to resolve their international disputes through arbitration, which is judged privately and universally accepted.